2011
DOI: 10.1111/j.1742-4658.2010.07966.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of N‐glycans of the planarian Dugesia japonica

Abstract: To investigate the relationship between phylogeny and glycan structures, we analyzed the structure of planarian N‐glycans. The planarian Dugesia japonica, a member of the flatworm family, is a lower metazoan. N‐glycans were prepared from whole worms by hydrazinolysis, followed by tagging with the fluorophore 2‐aminopyridine at their reducing end. The labeled N‐glycans were purified, and separated by three HPLC steps. By comparison with standard pyridylaminated N‐glycans, it was shown that the N‐glycans of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 21 publications
(28 reference statements)
1
35
1
Order By: Relevance
“…Quantitative Analysis of Sialylated Glycans by Anion Exchange HPLC-The prepared PA oligosaccharides treated with or without neuraminidases were subjected to an HPLC system equipped with a TSKgel DEAE-5PW column (7.5 ϫ 75 mm; Tosoh) and analyzed as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative Analysis of Sialylated Glycans by Anion Exchange HPLC-The prepared PA oligosaccharides treated with or without neuraminidases were subjected to an HPLC system equipped with a TSKgel DEAE-5PW column (7.5 ϫ 75 mm; Tosoh) and analyzed as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
“…Another study investigating the primary structures of two biantennary N-glycans of the glycoprotein from Rapana venosa (marine snail) hemocyanin showed that the glycans contain a 3-O-methyl group on the terminal Gal and/or GlcNAc (58). A terminal 3-O-MeMan was also found in N-glycans from the gastropod Arion lusitanicus (61) and from the planarian Dugesia japonica (62).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported methylated sugars as constituents of glycoproteins in other organisms, including nematodes, yeasts, snails, algae, and planarians (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). For example, in the study by Hall et al (52), 3-O-MeGal was found in hemocyanin from Helix pomatia (Roman snail), and both 3-O-MeGal and 3-O-MeMan were identified in hemocyanin from Lymnaea stagnalis (a freshwater snail).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were run on 12.6% gels. The separated proteins were transferred to PVDF membranes, followed by immunodetection with antibodies against phospho-p44/42 MAPK (Thr Purification and Structural Analysis of N-Glycans-Preparation and purification of pyridylaminated (PA-)N-glycans from glycopeptides derived from TIB-141 were carried out as described previously (25,26), except that the PA-glycans were first subjected to affinity chromatography on an hG9Null-immobilized column as described above. PA-glycans dissolved in TBS were applied to the column.…”
Section: Methodsmentioning
confidence: 99%
“…S3). Structural analysis of the PA-N-glycans was carried out according to the method of Natsuka et al (25) (i.e. consecutive glycosidase digestion and RP-HPLC analysis).…”
Section: Methodsmentioning
confidence: 99%